Development of a Data-Based Customer Relationship Management (CRM) Model to Increase Customer Loyalty in the E-commerce Sector - Loso Judijanto; Heppy Agustiana Vidyastuti; Rini Hadiyati; Mesak Yandri Masela (West Science Information System and Technology, 2024)
The rapid growth of the e-commerce sector has intensified the need for effective Customer Relationship Management (CRM) systems to enhance customer loyalty. This study aims to develop a data-based CRM model tailored for the e-commerce industry, emphasizing the integration of personalized communication, data-driven insights, and responsiveness. A quantitative approach was employed, with data collected from 60 respondents using a Likert scale of 1 to 5. The data were analyzed using SPSS version 25. Findings reveal significant positive relationships between CRM components and customer loyalty, with data-driven insights emerging as the most influential predictor. This study contributes to the literature by providing actionable insights and a validated framework for leveraging CRM practices in e-commerce. The findings underscore the importance of data integration, personalization, and responsive customer engagement to foster loyalty and gain a competitive advantage in the evolving digital marketplace.